A Survey Study of Students’ Motivation in English Language Learning - Andi Mangnguntungi Sudirman; Rusdiana Junaid; Wilhelmus Gon (BATARA DIDI : English Language Journal, 2022)
The purpose of this paper was to determine (1) the degree of students' motivation in English language learning and (2) the dominating motive between instrumental and integrative motivation in English language learning. This study was carried out at SMAN 1 Palopo. Mixed technique, which is mostly quantitative, was used, with a survey using an online Likert scale questionnaire administered to 31 respondents and five of them interviewed. The data has been evaluated quantitatively and statistically using the paired sample t-test and qualitative description. The questionnaire was examined according to the proportion of each response. To convert questionnaire data into percentages, the researcher multiplied the number of occurrences by 100 percent and then divided by the total number of respondents. The findings of this study reveal that SMAN 1 Palopo students have strong instrumental and integrative motivation, with a mean score of 4.12, when it comes to studying English. According to the results of the questionnaire survey, students' responses of agreement and strong agreement predominated, whereas responses of disagreement and severe disagreement did not occur considerably. The overall findings of the study indicate that students' English-learning motivation is mostly integrative. This indicates that students study English based on their initiative and desire to grasp and learn more about English culture.